The mural painting of the city of Sogamoso and the construction of the public (REVISTA NODO, 2024)
The purpose of this work is to account for the narratives and the transformation of public space, manifested in the mural painting in the Colombian city of Sogamoso. For this we have referred, as a source of analysis, to a previous theoretical and historical approach, as well as to the photographic record. Thus, unprecedented results are obtained in the study of the city and its relationship with the construction of its public spaces by artistic collectives. On the other hand, the artistic aspect —still very little recognized— is affirmed as an extension of the reality of the city itself. It is concluded how mural painting, in a visual laboratory, preferably defines urban art, and creates identity, memory and a city thought through citizen participation.
Keywords: art and city; public space; urban history